Strengthening Understanding of Sharia Finance and Dissemination of Sharia Bank Products for the Community of Tanjung Rema Darat Martapura - Aisyah, Lisda; Mardini, Yulida; Dairobi (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
Community service activities are one of the efforts to carry out the Tri dharma of Higher Education, which includes education, research and community service. Therefore the Faculty of Islamic Economics and Business at the Martapura Darussalam Martapura Islamic Institute in 2023 has a community service program organized by lecturers in accordance with the Institute's Vision and Mission. In this program, we carry out community service activities entitled